Urban networks: Connecting markets, people, and ideas*. (March 2016) - Glaeser, Edward L.; Ponzetto, Giacomo A. M.; Zou, Yimei; Meijers, Evert; Burger, Martijn
Abstract: We study the tradeoff between megacities and networks of smaller cities in a model of recombinant growth and endogenous amenities. Three factors are key: local returns to scale in innovation, the housing supply elasticity and the importance of local amenities. Even with global increasing returns, local returns to scale in innovation may be decreasing, making networks more appealing. Inelastic housing supply makes density costlier and may explain why networks are more popular in Europe than the US. Megacities can prevail thanks to amenities if the benefits of scale overwhelm the costs of density. The skilled are more likely to prefer megacities than the unskilled. Megacities may have short‐run costs yet improve upon networks in the long run.